Pengaruh Fermentasi Sari Kedelai dengan Lactobacillus sp. terhadap Kadar dan Profil Kromatografi Lapis Tipis Genistein serta Formulasinya dalam Granul Efervesen - LATIFAH RAHMAN; HUSNUL WARNIDA; NATSIR DJIDE (Fakultas Farmasi Universitas Pancasila, 2012)
lsoflavones in soybean and unfermented soybean product are in glycoside form which could not be absorbed by the body and should be hydrolyzed before it is metabolized. Hydrolysis by bacteria producing β-glucosidase occur throughout the gastrointestinal tract. Probiotic microorganisms, like Lactobacillus and bfiidobacterium, have an endogenous enzyme , β-glucosidase that plays an important role in changing the profile of isoflavones during fermentation. The study was to investigate TLC profile and genestein content in fermented soybeanmilk and to formulate the freeze-dried fermented soybeanmilk into effervescent granules preparation. Soybeanmilk was fermented with Lactobacillus sp., and then freeze-dried. The soybeanmilk, before and after fermentation, were then extracted and analyzed by TLC-scanner. The freeze-dried fermented soymilk was prepared into four formulations of effervescent granules with variations in citric acid-tartaric acid ratio. Granules were prepared by the wet method and theirs physical characteristics were evaluated. Extracted granules were analyzed by TLC-scanner. Genistein content in the fermented soymilk has increased 145,32% as compared to the unfermented soymilk. All four effervescent granules have good physical characteristics except that the moisture content were above 0.7%. Formula containing citric acidtartaric acid ratio of (1 : 1) produced effervescent granules with the best physical characteristics.